Converged Digital TV Services: The Role of Middleware and Future Directions of Interactive Television - Emmanuel Tsekleves; John Cosmas; Amar Aggoun; Jonathan Loo (International Journal of Digital Multimedia Broadcasting)
The subject of the future of the interactive Television medium has become a topic of great interest to the academic and industrial communities particularly since in the recent years there has been a dramatic increase in the pace of innovation of convergence of digital TV systems and services. The purpose of this paper is to provide a brief overview of what we know as digital TV converged services, to present and categorise the digital Television middleware technologies that contributed to it, and to present possible future trends and directions. A new Television era of converged wireless and mobile content delivery, user-authored content, multimodal interaction, intelligent personalisation, smart space awareness, and 3D content sensations is foreseen, creating ambient and immersive experiences.